Necrotizing Pancreatitis Secondary to Dulaglutide Use - Bhat, Salman Zahoor (J Endocr Soc, 2021)
Introduction/ Background: GLP-1 agonists are an essential component of the anti-diabetes armamentarium. Common side effects include mild gastrointestinal distress and headaches. Uncommon side effects include acute pancreatitis and can limit use. We report a case of acute severe necrotizing pancreatitis most likely attributed to dulaglutide. Clinical Case: A 69-year-old man presented lethargic with diffuse abdominal pain associated with nausea and vomiting of 1-day duration. His past medical history consisted of type 2 diabetes, hyperlipidemia, hypertension, and hypothyroidism. His diabetes regimen included metformin, glipizide, and empagliflozin. Dulaglutide was added three months prior at 0.75 mg weekly, and the dose was increased to 1.5 mg weekly three days before presentation, the patient having received one such dose. Initial workup showed lipase 2800 units/mL, amylase 1185 units/mL, lactate 12.6 mmol/L, white blood cells 20 x 10(9)/L, glucose 348 mg/dL, AST 30 unit/L, hematocrit 51.5%, blood urea nitrogen 24 mg/dL, and serum creatinine 1.57 mg/dL, calcium 8.1 mg/dL. No stones or CBD dilation were noted on ultrasound. Initial CT showed an enlarged pancreas with peripancreatic stranding and slightly diminished enhancement consistent with early signs of necrotizing pancreatitis. The patient became increasingly hypoxic and hypotensive and required intubation and triple pressor support to maintain adequate perfusion. On the second day of hospitalization, his hematocrit was 35.7%, blood urea nitrogen 37 mg/dL, calcium 6.8 mg/dL, and bicarbonate 21 mmol/L. AST and ALT peaked at 209 and 398 unit/L respectively. Calculated 48 hours Ranson’s score was 7. He completed 7 days of meropenem for necrotizing pancreatitis. He developed cholecystitis secondary to inflammatory damage of the biliary tract and received a cholecystostomy tube. A follow-up CT scan 7 days after the initial scan showed a prominent pancreas with extensive inflammation and without cysts, with several areas of nonenhancement/poor perfusion in the pancreatic head consistent with pancreatic necrosis. The patient made a full recovery and was discharged to a rehabilitation unit. Investigation into other causes of pancreatitis revealed triglycerides 104 mg/dL, a normal distribution of IgG subclasses (IgG4 36 mg/dL), no significant alcohol use, and no family history of pancreatitis. Conclusion: Pancreatic safety studies of dulaglutide have shown a good safety profile(1). However, FDA safety warning exists on GLP-1 agonist prescriptions. Necrotizing pancreatitis with GLP-1a is rarely reported. We present a case of severe necrotizing pancreatitis due to dulaglutide use with the existence of temporality, after ruling out other causes of pancreatitis. Reference: 1. Nauck MA et al. Assessment of Pancreas Safety in the Development Program of Once-Weekly GLP-1 Receptor Agonist Dulaglutide. Diabetes Care 2017;40:647–54.